Synthesis, characterization and applications of maghemite beads functionalized with rabbit antibodies - Rodriguez, A. F.R.; Rocha, C. O. [UNESP]; Piazza, R. D. [UNESP]; Dos Santos, C. C. [UNESP]; Morales, M. A.; Faria, F. S.E.D.V.; Iqbal, M Zubair; Barbosa, L.; Chaves, Y. O.; Mariuba, L. A.; Jafelicci, M. [UNESP]; Marques, R. F.C. [UNESP] (IOP Publishing, 2018)
Magnetic nanoparticles (NPs) have attracted great attention owing to their applications in the biomedical field. In the present work, maghemite (γFe2O3) NPs of 6.5 nm were prepared using a sonochemical method and used to prepare magnetic beads through silanization with 3-aminopropyltrimethoxysilane (APTS). Subsequently, amino groups in the resulting APTS-γFe2O3 beads were converted to carboxylic acid (CARB-γFe2O3) through the succinic anhydride reaction, as confirmed by transmission electron microscopy (TEM), Fourier transform infrared spectroscopy and dynamic light scattering (DLS) measurements. The size of these beads was measured as 12 nm and their hydrodynamic diameter as 490 nm, using TEM analysis and DLS, respectively. The CARB-γFe2O3 beads were further functionalized by immobilizing rabbit antibodies on their surfaces; the immobilization was confirmed by flow cytometry and ionic strength. The samples were further characterized by Mössbauer spectroscopy and DC magnetization measurements. Studies on magnetic relaxivities showed that magnetic beads present great potential for application in MR imaging.
Keywords: flow cytometry; magnetic nanobeads; mossbauer spectroscopy; MRI; rabbit antibody; XRD